Simulation of CIRNO-C2008 wheat yield in the Yaqui Valley using AquaCrop - Cora-Gil, Roberto; Orozco-Campos, Arturo Francisco; Ayala-Zepeda, Marisol; Parra-Cota, Fannie Isela; Estrada-Alvarado, María Isabel; de los Santos-Villalobos, Sergio (Revista Mexicana de Ciencias Agrícolas, 2025)
Worldwide, wheat is one of the most widely used cereals in the human diet and, in Mexico, it ranks second in production after corn. Nevertheless, its productivity is affected by the low efficiency of chemical fertilizers and the loss of nutrients in the soil, leading to environmental problems. It is necessary to look for alternatives to reduce the use of inorganic fertilizers and maintain or improve crop yield without affecting grain quality. This study calibrated and validated the AquaCrop simulation model for wheat crop development and yield. Experiments were carried out in the Yaqui Valley, Mexico, during the 2019-2020 cycle with the wheat (Triticum turgidum L.) variety CIRNO C2008 under different doses of nitrogen using urea (240, 120, and 0 kg N ha-1) to evaluate the impact of nutritional stress on crop development and yield. The analysis of variance showed that there were no significant differences (p< 0.05) between the simulated yields (7 189 t ha-1, 6 638 t ha-1 and 4 436 t ha-1 for the doses of 240, 120 and 0 kg N ha-1, respectively) and the observed yields (7.2 ±0.007 t ha-1, 6.6 ±0.02 t ha-1, 4.21 ±0.16 t ha-1, respectively). The results demonstrated that the yield simulation model for wheat crops was successfully calibrated using AquaCrop.
Keywords: plant physiology; soil fertility; stress; sustainability